A spectroscopic approach to detect and quantify phosmet residues in Oolong tea by surface-enhanced Raman scattering and silver nanoparticle substrate. (15th May 2020) - Chen, Xi; Wang, Danhong; Li, Jie; Xu, Taotao; Lai, Keqiang; Ding, Qi; Lin, Hetong; Sun, Lin; Lin, Mengshi
Highlights: Spherical and monodispersed AgNPs were synthesized for SERS measurement. SERS based on AgNPs generated strong enhancement of Raman signals. Detection limit of phosmet in Tieguanyin Oolong tea was 0.1 mg/kg. SERS based on AgNPs is a novel tool for detecting phosmet in Oolong tea. Abstract: There have been increasing concerns among consumers about pesticide residues in Oolong tea. This study aimed to establish surface-enhanced Raman scattering (SERS) method for rapid measurement of chemical contaminants in Oolong tea. Synthesis of SERS substrate was achieved by synthesizing silver nanoparticles (AgNPs) via a reduction method. AgNPs were spherical and highly monodispersed, which created remarkable electromagnetic fields during SERS activities to measure phosmet in the methanol-water solution and Oolong tea. Partial least squares regression models were established to predict the concentrations of phosmet in the methanol-water solution ( r = 0.934; slope = 0.880; RMSEP = 1.001 mg/L) and Oolong tea samples ( r = 0.927; slope = 0.938; RMSEP = 1.157 mg/kg) with the detection limit of 0.1 mg/kg. The results indicate that SERS coupled with silver nanoparticles is a fast, sensitive, and reliable method for detection and characterization of pesticide contaminants in Oolong tea products.